Využití elektroanalytických metod v potravinářské a farmaceutické analýze - Jashari, Granit (Univerzita Pardubice, 2023)
The main purpose of the research conducted within the frame of this doctoral thesis was to develop new electroanalytical approaches and methods applicable in food and pharmaceutical analysis. Due to the importance of the presence of lipophilic vitamins in food and pharmaceutical formulations, the simultaneous detection of lipophilic vitamins (A, E and K), and related compounds had been the primary goal of the dissertation. Since lipophilic analytes are usually occurring in complex matrices, the simplification of real samples treatment prior the analysis and elimination of toxic organic solvents in comparison with the previous methods have been the other benefits of this work. In addition, the development of low-cost and easy-to-use disposable sensors for the determination of selected biologically active compounds was yet another target of the whole research.
Application of electroanalytical methods in food and pharmaceutical analysis
Keywords: lipofilní vitaminy; potraviny; farmaceutika; voltametrie; elektrody a sensory; lipophilic vitamins; foodstuffs; pharmaceuticals; voltammetry; electrodes and sensors